2021
DOI: 10.1186/s13018-021-02842-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoma drynariae total flavonoids combined with calcium carbonate ameliorates bone loss in experimentally induced Osteoporosis in rats via the regulation of Wnt3a/β-catenin pathway

Abstract: Background Rhizoma drynariae, a traditional Chinese herb, is commonly used in treatment of bone healing in osteoporotic fractures. However, whether the Rhizoma drynariae total flavonoids (RDTF) can promote the absorption of calcium and enhance the bone formation is unclear. The aim of the present study was to investigate the preventive effects of RDTF combined with calcium carbonate (CaCO3) on estrogen deficiency-induced bone loss. Methods Three-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For instance, Hu et al investigated the preventive effects of total flavonoids of Drynariae Rhizoma (TFDR) combined with CaCO3 on bone loss caused by estrogen deficiency. The results showed that TFDR can increase OPG content, reduce the content of RANK and RANKL, improve the bone loss of OVX rats, and promote the repair of fractured trabecular bone in OVX rats ( Hu et al, 2021 ). TFDR also improved serum reactive oxygen species in OVX rats, SOD, and GSH-Px, reduced MDA, TNF-α, IL-6, and IL-1β levels, upregulated the expression of Runt-related transcription factor 2 (Runx2), OPG, and BGP, and downregulated the expression of p-AKT, p-PI3K, and p-mTOR, indicating that TFDR has anti-osteoporosis effects by enhancing the antioxidant capacity of rats ( Mu et al, 2021 ).…”
Section: Kidney Tonifying Traditional Chinese Medicine In the Treatme...mentioning
confidence: 99%
“…For instance, Hu et al investigated the preventive effects of total flavonoids of Drynariae Rhizoma (TFDR) combined with CaCO3 on bone loss caused by estrogen deficiency. The results showed that TFDR can increase OPG content, reduce the content of RANK and RANKL, improve the bone loss of OVX rats, and promote the repair of fractured trabecular bone in OVX rats ( Hu et al, 2021 ). TFDR also improved serum reactive oxygen species in OVX rats, SOD, and GSH-Px, reduced MDA, TNF-α, IL-6, and IL-1β levels, upregulated the expression of Runt-related transcription factor 2 (Runx2), OPG, and BGP, and downregulated the expression of p-AKT, p-PI3K, and p-mTOR, indicating that TFDR has anti-osteoporosis effects by enhancing the antioxidant capacity of rats ( Mu et al, 2021 ).…”
Section: Kidney Tonifying Traditional Chinese Medicine In the Treatme...mentioning
confidence: 99%
“…Calcium supplementation may be an effective treatment for osteoporosis. However, calcium supplements alone are ineffective in preventing osteoporosis and can even increase the risk of fractures [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TFDR is broadly used for osteoporosis treatment. Currently, the researches about the efficacy of TFDR mainly aim to treat postmenopausal osteoporosis (PMOP) and its action mechanism on growth of bone graft and fracture healing (10)(11)(12). However, TFDR has not been reported to cure GIOP yet.…”
Section: Introductionmentioning
confidence: 99%